Attitudes of university students towards digital (electronic) journalism in light of its competition for websites - Taghreed Fadel Hussein (Journal of Madenat Alelem University College, 2022)
The research deals with the role of electronic media in the educational process in light of the Corona pandemic, and aims at the extent to which university students use electronic media in the educational process during the Corona pandemic, and the extent to which university students follow educational materials through electronic media, and students’ evaluation of educational materials provided through electronic media, and the extent of the contribution of university students to educational materials through electronic media. Electronic media in opening new horizons for the purpose of communication between the teacher and the student. And it reached several results, including that the respondents consider education through electronic media as a field for scientific communication between the professor and the student, and that the respondents benefited from the experience of education through electronic media, and that the most important obstacles that prevent the use of education through electronic media as an effective medium in order to support the educational process during the Corona pandemic Turns out the internet is weak.